2015
DOI: 10.1021/acs.accounts.5b00025
|View full text |Cite
|
Sign up to set email alerts
|

From One to Many: Dynamic Assembly and Collective Behavior of Self-Propelled Colloidal Motors

Abstract: S Supporting Information CONSPECTUS: The assembly of complex structures from simpler, individual units is a hallmark of biology. Examples include the pairing of DNA strands, the assembly of protein chains into quaternary structures, the formation of tissues and organs from cells, and the self-organization of bacterial colonies, flocks of birds, and human beings in cities. While the individual behaviors of biomolecules, bacteria, birds, and humans are governed by relatively simple rules, groups assembled from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
267
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(271 citation statements)
references
References 78 publications
3
267
0
1
Order By: Relevance
“…First, they can help to understand the main underlying physical principles governing the collective motion of active microscopic individuals which share similar physical properties, namely self-propulsion, rotational diffusion, and low-Reynolds-number hydrodynamics, as well as short-range and phoretic interactions [5]. Second, the self-assembly of interacting active colloids offers the possibility of forming a new class of active materials with novel and tunable properties [35,286].…”
Section: Collective Dynamicsmentioning
confidence: 99%
“…First, they can help to understand the main underlying physical principles governing the collective motion of active microscopic individuals which share similar physical properties, namely self-propulsion, rotational diffusion, and low-Reynolds-number hydrodynamics, as well as short-range and phoretic interactions [5]. Second, the self-assembly of interacting active colloids offers the possibility of forming a new class of active materials with novel and tunable properties [35,286].…”
Section: Collective Dynamicsmentioning
confidence: 99%
“…[28] Currently, the behavior of individual active particles is well documented and mostly understood. However, as this field advances, greater emphasis is being placed upon investigating and engineering the interactions between swimmers, [4,[29][30][31][32][33] for the next wave of advanced applications. The majority of the available studies on the interactions between active colloids have demonstrated selfassembly via direct contact excluded volume interactions and through powered motility of the mobile entities, [34][35][36][37] e.g., the particles come into contact to form self-assembled clusters that translate and rotate.…”
Section: Contactless Assemblymentioning
confidence: 99%
“…We did not magnetize the particles before dispersal as magnetized Janus spheres were observed to rapidly self-assembled as a result of their permanent dipoles from the ferromagnetic Ni. However, as this field advances, greater emphasis is being placed upon investigating and engineering the interactions between swimmers, [4,[29][30][31][32][33] for the next wave of advanced applications. We note this alignment of the Janus director in the absence of a magnetic field is due to interactions between the particles and the solid boundary.…”
mentioning
confidence: 99%
“…Examples include supramolecular assemblies ( 2 ), various active colloids ( 3 , 4 ), millimeter spinning discs ( 5 , 6 ), and ferrofluid droplets ( 7 ). These works are driven mostly by two main quests.…”
Section: Introductionmentioning
confidence: 99%